ANALYZING ERRORS IN BUSINESS ENGLISH COVER LETTERS - purnamasari, jelita (English Edu: Journal of English Teaching and Learning, 2024)
This descriptive qualitative research investigated the common errors in business English letters especially cover letter written by Business Administration students and also explores the challenges faced by Business Administration students in writing cover letters. The sample consisted of 10 students, whose letters were analyzed. 10 cover letters written by Business Administration students at IISIP YAPIS Biak was the primary instrument for data collection, which was analyzed systematically to identify errors related to grammatical errors, lexical choice, pragmatic errors, and generic content. Further, the thematic analysis was used to investigated the students’ writing habit and challenges. The data was collected used interviews. The analysis focused on identifying recurring themes. The findings showed that the common errors in students’ cover letters were grammatical errors, lexical choice, pragmatic errors, and generic content while the significant challenges faced by Business Administration students in writing cover letters, including procrastination, minimal revision practices, language proficiency issues, vocabulary limitations, and difficulty in maintaining a formal tone. These challenges are deeply rooted in students' writing habits and educational experiences.